Learning for Scientific Culture by Using Interactive Whiteboard According to the Faculty of the University of Baghdad Viewpoint (Journal of the College of Education for Women, 2019)
The progress of science in all its branches and levels made great civilized changes ofour societies in the present day, it's a result of the huge amount of knowledge, the increase ofnumber of students, and the increase of community awareness proportion of the importance ofeducation in schools and universities, it became necessary for us as educators to look atscience from another point of view based on the idea of scientific development of curriculaand teaching methods and means of education, and for the studying class environment as awhole, by computer and internet use in education to the emergence of the term educationtechnology, which relies on the use of modern technology to provide educational content tothe learner in a manner appropriate and effective at the same time. "Interactive whiteboard" isone of the new educational technology means; it is a flat screen delicate texture, works inconjunction with computers and a data projector "Data Show" and converts it into an effectivetool for education.This study aimed to identify the faculty members viewpoint about the use ofinteractive (Smart) whiteboard. The study sample consisted of 200 of teaching staff of theCollege of Education for Women and the College of Science for Women at the University ofBaghdad, the researchers used measure of attitudes towards the use of the blackboard andrelied on the recurrence and percentages as a statistical treatment.The study results showed the following:1. There was approval towards the use of smart board. Responses and that the teachersexperienced 5 years towards the use of smart board more than responses of the teachersexperienced from 6-10 years.2. There was no difference in the responses of the sample towards the use of smart boardattributed to age.